2020
DOI: 10.1002/cti2.1223
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin and abundant TCR stimulation are required for the generation of stable human induced regulatory T cells

Abstract: Objectives Regulatory T cells (Tregs) are a vital sub‐population of CD4+ T cells with major roles in immune tolerance and homeostasis. Given such properties, the use of regulatory T cells for immunotherapies has been extensively investigated, with a focus on adoptive transfer of ex vivo expanded natural Tregs (nTregs). For immunotherapies, induced Tregs (iTregs), generated in vitro from naïve CD4+ T cells, provide an attractive alternative, given the ease of generating cell numbers required for clinical dosage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 95 publications
(221 reference statements)
0
6
0
Order By: Relevance
“…The majority of published protocols for TGF‐β‐induction of human iTregs from naïve CD4 + T cells use between 1 and 5 ng mL −1 of TGF‐β . 21 , 22 , 23 We tested TGF‐β at concentrations from 1 to 100 ng mL −1 and confirmed that maximal FOXP3 expression (as determined by both the percentage of positive cells and MFI) had occurred by 1 ng mL −1 (dose curve data in Figure 1 ). This equates to 0.04 n m, as activated TGF‐β exists as a 25 kDa dimer, thus 1 ng mL −1 TGF‐β was selected as our comparison condition for the study.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…The majority of published protocols for TGF‐β‐induction of human iTregs from naïve CD4 + T cells use between 1 and 5 ng mL −1 of TGF‐β . 21 , 22 , 23 We tested TGF‐β at concentrations from 1 to 100 ng mL −1 and confirmed that maximal FOXP3 expression (as determined by both the percentage of positive cells and MFI) had occurred by 1 ng mL −1 (dose curve data in Figure 1 ). This equates to 0.04 n m, as activated TGF‐β exists as a 25 kDa dimer, thus 1 ng mL −1 TGF‐β was selected as our comparison condition for the study.…”
Section: Resultsmentioning
confidence: 69%
“… 32 Future studies should investigate the epigenetic and functional effects on Tregs induced with Hp‐ TGM without CD28 co‐stimulation. However, as recent studies of iTregs generated by TGF‐β and all‐ trans retinoic acid and rapamycin 22 ; or TGF‐β and small molecule inhibitors 23 ; or lentiviral transfer of FOXP3 33 ; have found that the iTregs had robust and stable suppressive function without acquiring a methylated TSDR, this feature may not be essential for suppressive function of iTregs. Nevertheless, our data showing increased H3K27ac marks in the FOXP3 locus in Hp ‐TGM‐induced Tregs suggest that this molecule may drive epigenetic changes that promote Treg stability 34 and warrant further investigation.…”
Section: Discussionmentioning
confidence: 98%
“…This associates with significant costs and specific technical requirements ( 25 ). Additionally, repeated treatments for the patient are often required, since ex vivo -expanded Tregs can become instable over time ( 26 ). Finally, chronic inflammation in autoimmune patients promotes the reversal of the phenotype of the transferred Tregs into T effector cells ( 27 ), and Treg potency may decrease over time ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the beneficial effects of rapamycin (sirolimus) on Tregs has been extensively explored 170,171 . Rapamycin can also synergize with TGF‐β1 and/or retinoic acid to promote Treg induction from Tconvs 172,173 . Accordingly, in a mouse model of heterotopic heart transplant, A2‐CAR Tregs synergized with rapamycin to prolong allograft survival compared to either monotherapy 174 .…”
Section: ‐Beyond: the Advanced Engineering Era And Into The Clinicmentioning
confidence: 99%
“…170,171 Rapamycin can also synergize with TGF-β1 and/or retinoic acid to promote Treg induction from Tconvs. 172,173 Accordingly, in a mouse model of heterotopic heart transplant, A2-CAR Tregs synergized with rapamycin to prolong allograft survival compared to either monotherapy. 174 Furthermore, 4-1BB-CAR Tregs, which are more likely to destabilize into FOXP3 − Helios − as a result of mTOR pathway overactivation, can be restabilized using rapamycin and vitamin C. 175 Another drug, cyclophosphamide, which is used to prevent acute GVHD after hematopoietic stem cell transplant and condition people for CAR T cell therapy, may also have beneficial effects on Tregs.…”
Section: Into the Clinicmentioning
confidence: 99%